A Comprehensive Strategy Formulation for Business Sustainability: A Case Study of a Coal Mining Company - Nurjanah, Novia Siti; Valdiansyah, Ryan Harbi; Rahayu, Sri (Universitas Pamulang, 2024)
The aim of this study is to evaluate the comprehensive strategy formulation of PT XYZ, an Indonesian coal mining company, by applying the IFE-EFE and QSPM methods. The research involved interviews with 10 senior management members from various divisions to obtain a holistic view of the company. The findings showed that the most effective strategy to boost sales during the current period is the optimal one among the four strategies identified through QSPM analysis. This study's results are expected to strengthen the sustainability of coal mining companies by improving management strategies through corporate strategy analysis. The researchers acknowledge the limitations in expanding the strategies used in the SWOT analysis, offering future researchers the chance to develop more comprehensive IPO development indicators as needed.